Science Fiction and Speculative Fiction Challenging Genres - Thomas, P. L.; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2013)
Why did Kurt Vonnegut shun being labeled a writer of science fiction (SF)? How did Margaret Atwood and Ursula K. Le Guin find themselves in a public argument about the nature of SF? This volume explores the broad category of SF as a genre, as one that challenges readers, viewers, teachers, and scholars, and then as one that is often itself challenged (as the authors in the collection do). SF, this volume acknowledges, is an enduring argument. The collected chapters include work from teachers, scholars, artists, and a wide range of SF fans, offering a powerful and unique blend of voices to scholarship about SF as well as examinations of the place for SF in the classroom. Among the chapters, discussions focus on SF within debates for and against SF, the history of SF, the tensions related to SF and other genres, the relationship between SF and science, SF novels, SF short fiction, SF film and visual forms (including TV), SF young adult fiction, SF comic books and graphic novels, and the place of SF in contemporary public discourse. The unifying thread running through the volume, as with the series, is the role of critical literacy and pedagogy, and how SF informs both as essential elements of liberatory and democratic education.
Keywords: Education; Education; Education (general).